Molecular Dynamics Investigations Suggest a Non-specific Recognition Strategy of 14-3-3σ Protein by Tweezer: Implication for the Inhibition Mechanism - Shi, Mingsong; Xu, Dingguo (Frontiers in Chemistry, 2019)
Supramolecular complex formed between protein and designed molecule has become one of efficient ways to modify protein functions. As one of well-studied model systems, 14-3-3 family proteins play an important role in regulating intracellular signaling pathways via protein-protein interactions. In this work, we selected 14-3-3 as the target protein. Molecular dynamics simulations and binding free energy calculations were applied to identify the possible binding sites and understand its recognition ability by one of supramolecular inhibitors, tweezer molecule (CLR01). On the basis of our simulation, major interactions between lysine residues and CLR01 come from the van der Walls interactions between the long alkyl chain of lysine and the cavity formed by the norbornadiene and benzene rings of the inhibitor. Apart from K214, which was found to be crystallized with this inhibitor, other lysine sites have also shown their abilities to form inclusion complexes with the inhibitor. Such kind of non-specific recognition features of CLR01 against 14-3-3can be used in the modification of the protein functions via supramolecular chemistry.